QUALITY OF LIFE AND THERAPEUTIC ADHERENCE IN PATIENTS WITH GLAUCOMA FROM A HOSPITAL IN CALLAO - Elescano Salazar, Andy Rubén (2020)
Objective: To determine the quality of life and therapeutic adherence in patients with glaucoma at a Callao public hospital. Material and methods: A quantitative, correlational and cross-sectional study was carried out. The population consisted of 260 patients with a diagnosis of glaucoma who were cared for at a Callao public hospital during the year 2019. The technique used was the survey and the data collection instrument was the Glaucoma Quality of Life questionnaire (GQL -15) that evaluated the quality of life, and the Morisky-Green Test to measure therapeutic adherence. Results: The predominant quality of life was the severe level with 53.8% (n = 140), in relation to its dimensions the one that presented a more severe level was the mobilization outdoors with 74.2% (n = 193), followed by the of central and near vision with 66.2% (n = 172), adaptation to darkness and glare with 58.5% (n = 152) and peripheral vision with 55.4% (n = 144). In therapeutic adherence, the adherent predominated with 55.4% (n = 144), followed by the non-adherent with 44.6% (n = 116). In the inferential analysis of both variables, a Chi-square X2 value of 88.9215 and a p value <0.00001 were found, therefore, there is a significant relationship. Conclusions: There is a significant relationship between both variables. As for the quality of life, the severe level predominated and the adherent predominated in the therapeutic adherence.